Nikah Fasid dan Implikasinya terhadap Iddah Perspektif Madzhab Syafi’i - Habiburrahman, Muhammad; Sa’adah, Ummu (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2025)
This research aims to understand nikah fasid (invalid marriage) and its implications for iddah (waiting period) from the perspective of the Shafi’i school of thought. When a marriage is declared fasid or invalid, it leads to various legal consequences, including issues related to the status of children, mahram relationships, and one significant aspect—iddah. Iddah is a mandatory waiting period during which a woman is prohibited from remarrying, intended to confirm the emptiness of the womb, as an act of devotion, or as mourning for the deceased husband. Iddah is a prescribed obligation following a valid marriage. In the case of a fasid marriage, the implications differ, and this issue is often overlooked. This study uses a qualitative method with a library research approach and employs descriptive-analytical analysis. The primary data sources are Shafi’i fiqh books, while general fiqh books serve as secondary sources. The findings show that an invalid marriage has no legal effect if no sexual intercourse has occurred. However, if intercourse has taken place within the fasid marriage, iddah becomes obligatory for the woman.